2020
DOI: 10.1075/ts.00023.nun
|View full text |Cite
|
Sign up to set email alerts
|

Machine translation in the news

Abstract: Machine translation (MT) is now firmly in the public eye. The media can reflect and influence the public perception of MT and, by extension, of translation itself, but the news coverage of MT has to date remained largely unexplored. This study draws on the news framing literature to present an analysis of how MT is described in the written press. Based on a sample of 284 MT-focused newspaper articles, the news reporting on MT was found to be significantly more positive than negative. This positive framing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
2
1
0
1
Order By: Relevance
“…However, in the same study, the clients/users of translations demonstrated more positive assessment of the quality of machine translation compared to that of professional users (García, 2010 ). Our findings are also in line with the implications revealed by Vieira ( 2020 ) who concluded that there is a clear divide between the perceptions of professionals and non-professionals toward machine translation and its capabilities. In his study, Vieira acknowledged that the public coverage of machine translation veers more toward positive attitudes rather than negative.…”
Section: Discussionsupporting
confidence: 92%
“…However, in the same study, the clients/users of translations demonstrated more positive assessment of the quality of machine translation compared to that of professional users (García, 2010 ). Our findings are also in line with the implications revealed by Vieira ( 2020 ) who concluded that there is a clear divide between the perceptions of professionals and non-professionals toward machine translation and its capabilities. In his study, Vieira acknowledged that the public coverage of machine translation veers more toward positive attitudes rather than negative.…”
Section: Discussionsupporting
confidence: 92%
“…The findings presented in this article open a door to research on the social implications of this trend. Our findings echo the studies that demonstrate the largely negative attitudes of professional translators to MT, but show that a negative disposition toward MT is common also to end users who are not translators (which, interestingly, does not correspond to the largely superficial, positive framing of MT in the press, see Vieira, 2020b). Non-translator end users, despite being by far the main users of the technology, have been largely overlooked in sociological-oriented research of MT.…”
Section: Discussionsupporting
confidence: 81%
“…However, since law tends to be a local discipline, domain experts may be unaware of the pitfalls of legal translation. All this confirms that MT literacy is indeed much needed among lawyers, particularly among those who seem to believe in the overstated claims about MT capabilities (Vieira 2020) or fail to realise the ethical dimension of asking for "revision" of machine-translated texts. Much has been said about the ethics of translators (Chesterman 2001), and there are a growing number of discussions on various aspects of MT ethics (e.g.…”
Section: Discussionmentioning
confidence: 61%